Warehouse Location Decision in Pakistan:A Real Case Study - Khan, Sharfuddin Ahmed; Zaidi, Syed Adeel Haneef (International Journal of Supply Chain Management, 2013)
The manufacturing industry in Pakistan ispassing through a critical phase of its history. In the changing market placeconsumer are increasingly vigilant and demanding better quality, morecompetitive prices and shorter lead times. Maintaining cost effectivemanufacturing along with it distribution to the different customers across thecountry is becomes challenging day by day. In this paper, we propose anadditional new warehouse location in Pakistan using transportation cost as adecision factor. Initially the proposed warehouse will be run by the third partywarehouse service provider on temporary basis, so that it lower down theinventory level of Lahore warehouse from 0.4 million liters to 0.2 millionliters, saves approximately 1.5 Million Rs. / year with improved customerservice .